Islamic Boarding School: Institution of Character Education - Aswad Abdullah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Islamic boarding school (pesantren) is the forerunner of Islamic education institutions in Indonesia. The initial attendance of the pesantren was estimated from 300-400 years ago and reached almost all levels of the Indonesian Muslim community, especially on Java. After Indonesia gained its independence, especially since the transition to the New Order and when economic growth really increased sharply, pesantren education became more structured and pesantren curricula became better. This study aims to discuss the role of Islamic boarding schools in character building. This type of research is library research, namely research whose main object is books or other sources of literature. As an educational institution, Islamic boarding school are very concerned with the field of religion (tafaqquh fi al-din) and the formation of the nation's character which is characterized by morality. The provisions of religious education are explained in Article 30 Paragraph (4) of the National Education System Law that religious education is in the form of diniyah education, pesantren, and other similar forms. The existence of pesantren is an ideal partner for government institutions to jointly improve the quality of education and the foundation of the nation's character. This can be found from a variety of phenomena that occur such as fights between schools and distributors who are widespread and drug users among young people are rarely found they are boarding children or graduates of boarding schools. Keywords: Islamic boarding school, education, character